Clinical and Radiological Prognostication of Diffuse Axonal Injury - Viswanathan, Rajanandhan; Sethuraman, Devanand Senthil Kumar (Nepal Journal of Neuroscience, 2023)
Introduction:  We studied the efficacy of the admission neurological status (Glasgow Coma Score - GCS) and the radiological findings (Marshall, Rotterdam and MRI scoring systems) in prognostication of Diffuse Axonal Injury (DAI) using the Glasgow Outcome Score (GOS) to quantify the clinical outcome.Material and Methods: This is a prospective observational study of 158 consecutive Diffuse Axonal Injury (DAI) patients conducted at Madras Medical College. GCS at admission was taken as the clinical data. Marshall’s, Rotterdam and MRI scores were taken as radiological data. The patients’ GOS at 1 month was taken as clinical outcome.Statistical Analysis: Statistical analyses were then made to correlate the clinical and radiological data with the one-month outcome of the patients. Statistical analysis was done using the SPSS software – version 16 using statistical tests like Pearson’s coefficient and ANOVA. A p value of less than 0.05 was considered statistically significant.Results: The admission GCS and MRI grade of DAI showed a statistically significant correlation with the clinical outcome, but the Marshall and Rotterdam scores did not.Conclusion: Proper neurological evaluation of the patient with GCS score on admission and MRI brain when feasible, with both having a statistically significant correlation with clinical outcome, provide reliable prediction models for prognosticating outcome in DAI patients.